2017
DOI: 10.1038/s41467-017-01652-8
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Cortical dendritic activity correlates with spindle-rich oscillations during sleep in rodents

Abstract: In the originally published version of this Article, incorrect references were cited on two occasions in the Results section. Under the subheading 'Ca 2+ activity in single dendrites and somata of L5 neurons', the final sentence of the second paragraph incorrectly cited reference 29 instead of reference 31. Under the subheading 'Spiking of L5 cell bodies is not influenced by spindles', the first sentence cited reference 30 instead of reference 29. These errors have now been corrected in both the PDF and HTML v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Two recent findings suggest potential underlying mechanisms. An in vivo imaging study by Seibt et al recently described high levels of dendritic calcium influx (which occurred in a synchronized manner among neighboring cortical neurons) which was tightly linked to spindle frequency EEG activity [72]. Insofar as increasing dendritic calcium is a consistent correlate of (and indeed prerequisite for) LTP [73], this finding is completely consistent with other results linking spindle-frequency activity to synaptic potentiation in thalamocortical circuits.…”
Section: Messa DI Voce: Thalamocortical Sleep Spindlessupporting
confidence: 75%
See 1 more Smart Citation
“…Two recent findings suggest potential underlying mechanisms. An in vivo imaging study by Seibt et al recently described high levels of dendritic calcium influx (which occurred in a synchronized manner among neighboring cortical neurons) which was tightly linked to spindle frequency EEG activity [72]. Insofar as increasing dendritic calcium is a consistent correlate of (and indeed prerequisite for) LTP [73], this finding is completely consistent with other results linking spindle-frequency activity to synaptic potentiation in thalamocortical circuits.…”
Section: Messa DI Voce: Thalamocortical Sleep Spindlessupporting
confidence: 75%
“…Insofar as increasing dendritic calcium is a consistent correlate of (and indeed prerequisite for) LTP [73], this finding is completely consistent with other results linking spindle-frequency activity to synaptic potentiation in thalamocortical circuits. Critically, this increase in dendritic calcium was not associated with a concomitant increase in neuronal spiking during spindle-rich sleep [72]-suggesting a non-Hebbian form of EPSP-driven plasticity, dependent on intra-EPSP timing [74,75] during spindling. An explanation of the unique conditions found during spindles in the Seibt et al study (i.e.…”
Section: Messa DI Voce: Thalamocortical Sleep Spindlesmentioning
confidence: 85%
“…Through these cross-frequency interactions SSs could augment/prolong calcium conductance and trigger the signaling cascades required for consolidative plasticity. Seibt et al ( 2017 ) demonstrate that SS associated sigma activity elevates dendritic calcium, providing experimental evidence that systems memory consolidation associated oscillations can evoke changes in dendritic calcium kinetics/dynamics. In sum, interaction amongst dynamical brain rhythms orchestrates membrane properties to gate the synaptic plasticity necessary for consolidative mnemonic processing during sleep.…”
Section: Nrems Oscillations and Memory Consolidationmentioning
confidence: 98%
“…The relatively high oscillatory frequency of SSs makes these rhythms unlikely to trigger depressive STDP mechanisms. However, given that SSs have been demonstrated to elicit calcium transients in dendrites (Seibt et al, 2017 ) it is possible that particular SS waveforms, or SSs timed to occur in isolation from SPW-R or SO depolarizations, could cause the activation of depressive biochemical cascades.…”
Section: Nrems Oscillations and Forgettingmentioning
confidence: 99%
“…On the other hand, recent calcium imaging studies of the mouse neocortex have demonstrated higher activity of Sst+ interneurons in superficial cortical layers during wake versus NREM sleep (64,65). This effect (which would lead to reductions in dendritetargeted inhibition during sleep) may be related to the recent finding of dendritic calcium spikes in these cortical layers during NREM oscillations (66). Critically, the activation of neocortical Sst+ interneurons during active wakefulness is driven by cholinergic signaling (67).…”
Section: Neurosciencementioning
confidence: 99%